Modernizing Energy Services for the Poor : A World Bank Investment Review, Fiscal 2000-08 - Barnes, Douglas F.; Singh, Bipul; Shi, Xiaoyu (World Bank, Washington, DC, 2017)
The term energy access has various connotations to energy development specialists. For this review, we define energy access as relating both to physical proximity to energy infrastructure and to the policies and frameworks supporting the transition to better, reliable, and more efficient use of electricity and modern fuels. This viewpoint frames energy access as a development process sometimes referred to as the energy transition that starts with reliance on low-quality energy sources (straw, dung, candles) and finishes when high-quality energy sources, such as commercial fuels or electricity, are available. Access to these higher-quality energy sources allow for services (lighting, communication, cooling, pumping), which are not available at lower rungs of the energy ladder. This report focuses on the World Bank's portfolio of energy access-related projects approved during most of the past decade (FY2000-08). The objectives of the review were to compile an up-to-date data base on energy access-related assistance commitments and review current trends and patterns of energy access-related assistance. The authors also wanted to examine to the greatest extent possible the lessons that could be learned across regions, focusing on policy and project design recommendations. Finally, it was important to establish a solid methodology for measuring energy access in order to provide a baseline for future reviews of the investment portfolio. This study focuses on the World Bank's role in energy access investments for the period between fiscal years 2000 and 2008. Developing and transition countries face huge investments in energy access in order to meet their commitments to achieving the Millennium Development Goals (MDGs).